2014
DOI: 10.1371/journal.pone.0090960
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 and Soluble Interleukin-15 Receptor α in Coronary Artery Disease Patients: Association with Epicardial Fat and Indices of Adipose Tissue Distribution

Abstract: Interleukin-15 (IL-15) is a pro-inflammatory cytokine which signals via a specific alpha receptor subunit (IL-15Rα). Increased IL-15 level has been observed in cardiovascular patients and IL-15 immunoreactivity has been detected at vulnerable atherosclerotic plaques. Due to the association between adipose tissue distribution, inflammation and coronary artery disease (CAD), we quantified IL-15 and IL-15Rα in CAD patients with different adiposity and adipose tissue distribution and we evaluated whether epicardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
(40 reference statements)
1
31
0
Order By: Relevance
“…Fasting glucose, glycated hemoglobin (HbA1c), insulin, total cholesterol, and triglycerides were quantified with commercial kits using Cobas 6000 analyzer (Roche Diagnostics, Milan, Italy), as previously reported [16, 17]. Briefly, total cholesterol has been determined by an enzymatic-colorimetric method.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting glucose, glycated hemoglobin (HbA1c), insulin, total cholesterol, and triglycerides were quantified with commercial kits using Cobas 6000 analyzer (Roche Diagnostics, Milan, Italy), as previously reported [16, 17]. Briefly, total cholesterol has been determined by an enzymatic-colorimetric method.…”
Section: Methodsmentioning
confidence: 99%
“…These data, together with the high level of IL-15 expression in skeletal muscles following exercise, have led to the hypothesis that IL-15 may promote lean body mass [ 20 ]. Contrarily, other studies have reported increased expression of IL-15 in obesity and its induction by inflammatory cytokines in adipocytes [ 21 ]. Since IL-15 is induced by inflammatory stimuli, and several inflammatory cytokines such as IL-6, TNFα, IFNγ are implicated in promoting obesity and insulin resistance, we postulated that IL-15 might contribute to the pathogenesis of obesity rather than conferring protection against it.…”
Section: Introductionmentioning
confidence: 99%
“…IL-15 also exhibits proin ammatory and anti-in ammatory action in various tissues. It has both a positive anticancer effect through stimulation of NK cells and a deleterious effect associated with in ammatory bowel disease [26]. Brain-derived neurotrophic factor (BDNF) is known to be released mainly in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%